Brief Reports on KAISTSAT-4 Mission Analysis - J. Seon; K. I. Seon; S, H. Kim; K.-W. Min; B. J. Kim; R. C. K. Yong; L. F. Leong; H. J. Chun; H. S. Chang; H. S. Kim; J. S. Bae; Y. W. Choi; et al. (Journal of Astronomy and Space Sciences, 2000)
Five scientific instruments are planned on KAISTSAT-4 that is scheduled to be launch-ed in 2002. A far ultra-violet imaging spectrograph and a set of space plasma instruments are currently being designed. The imaging spectrograph will make observations of astronomical objects and Earth's upper atmosphere. The plasma instrumentation is capable of fast measuring the thermal magnetospheric plasmas, cold ionospheric plasmas and the Earth's magnetic fields. Major system drivers and constraints on the payloads as well as the spacecraft are identified. A preliminary analysis of the K-4 mission has been undertaken with the system requirements that are derived from the system drivers. Detailed investigation shows that Sun-synchronous orbits with approximate altitudes of 800 km are optimal to satisfy the identified requirements. Comparisons with other orbits of different inclinations are also shown. Four operation modes and a daily schedule of spacecraft maneuver are found from the Sun-synchronous orbital model. It is shown that the scientific objectives of K-4 can be achieved with moderate levels of design and operation risks.